Analysis of the Effect of Online Delivery Food on Customer Loyalty: Case Study on Kopi Kenangan Medan - Meiriza, Mica Siar; Sitanggang, Karolin Gabrela; Sinurat, Nadia Natalia; Rajagukguk, Nicko Fernando; Lingga, Desmila Atheja (ProBisnis : Jurnal Manajemen, 2025)
This study aims to examine the impact of online food delivery services on customer loyalty at the Kopi Kenangan branch in Medan Perjuangan. The rapid advancement of digital technology has facilitated the online food ordering process for consumers, which is crucial for fostering customer loyalty. This research employs a quantitative methodology using a survey approach, with a questionnaire distributed to 50 respondents who have utilized the online delivery service from Kopi Kenangan. Data analysis was conducted through validity and reliability tests, along with simple linear regression, t-tests, and F-tests to assess both partial and simultaneous effects of the independent variable on the dependent variable. The findings indicate that online food delivery services significantly influence customer loyalty, evidenced by an Fcount of 12.708, which exceeds the Ftable value of 3.18, and a significance level of 0.001. However, the coefficient of determination reveals that online delivery services account for only 39.3% of customer loyalty, suggesting that other factors, such as product quality and brand image, also contribute to enhancing customer loyalty. Therefore, Kopi Kenangan should focus on continuously improving the quality of their delivery services while also considering other elements that affect customer loyalty.